In Silico, SwissADME, and DFT Studies of Newly Synthesized Oxindole Derivatives Followed by Antioxidant Studies - Abdur Rauf; Haroon Khan; Momin Khan; Ali Abusharha; Goncagül Serdaroğlu; Maria Daglia (Journal of Chemistry)
The compounds were synthesized by refluxing 6-chlorooxindole with 2,3-dichlorobenzaldehyde and 2,6-dichlorobenzaldehyde in the presence of piperidine as a catalyst and characterized by spectroscopic analysis using 1H NMR, 13C NMR, and mass spectrometry as (E)-3-(2,3-dichlorobenzylidene)-6-chloroindolin-2-one (C-1) and (E)-3-(2,6-dichlorobenzylidene)-6-chloroindolin-2-one (C-2). Additionally, in silico ADME studies indicated that C-1 and C-2 with 1,1 rotatable bonds could have moderate water solubility and therefore could have the potential ability to cross the blood-brain barrier. Both showed high GI absorption, indicating that they are suitable for intestinal absorption while the compounds showed CYP1A2, CYP2C19, and CYP2C9 inhibition. The five drug-likeness criteria, which were Lipinski, Muegge, Ghose, Veber, and Egan, and the principles of drug-likeness are not violated by compounds C-1 and C-2. Also, the DFT computations were performed at the B3LYP level and at 6-311++G∗∗ basis set to evaluate and support the obtained results from the experiment. The FMO results revealed that C-1 could likely prefer the intramolecular interactions rather than the intermolecular interactions, and vice versa for C-2. In addition, the NBO results indicated that the resonance interaction, especially the shift of electron to empty orbitals from lone pair electrons of nitrogen, would contribute to the stabilization of both compounds greatly. In DPPH assay, the compounds showed IC50 values of 37.390 and 34.676 μM, respectively. Similarly, in ABTS assay, the calculated IC50 values for the compounds were 25.381 and 33.706 μM, respectively. In short, these results provided a solid ground for further preclinical studies in quest of new effective therapeutic agents.